Decarbonylation of Aromatic Aldehydes and Dehalogenation of Aryl Halides Using Maghemite-Supported Palladium Catalyst - Ajdačić, Vladimir; Nikolić, Andrea; Simić, Stefan; Manojlović, Dragan; Stojanović, Zoran; Nikodinovic-Runic, Jasmina; Opsenica, Igor M. (Synthesis, 2018)
A facile decarbonylation reaction of a variety of aromatic and heteroaromatic aldehydes using maghemite-supported palladium catalyst has been developed. The magnetic properties of catalyst facilitated an easy and efficient recovery of the catalyst from the reaction mixture using an external magnet. It was found that the catalyst could be reused up to four consecutive catalytic runs without a significant change in activity. In addition, the catalyst was also very effective in the dehalogenation of aryl halides. This is the first report on efficient utilization of directly immobilized Pd on maghemite in decarbonylation and dehalogenation reactions.
Keywords: decarbonylation; dehalogenation; palladium catalyst; maghemite; magnetically recoverable catalyst